Participação da comunidade no contexto escolar: expectativas e entendimento dos diretores, professores e funcionários de escolas públicas estaduais de Franca - ciclo I - Machado, Maria Luiza Franco Nery (2008)
This research aimed at investigating, through the education professionals point of view, how parents/guardian are participating at school, what professionals expect from this participation and which factors could damage or help its promotion. Two auxiliary canals at Public State Schools: Parent and Teacher Associations (PTAs) and School Councils were approached as they are in force and guaranteed by law. Fourteen subjects (directors, teachers and employees), from seven Elementary Schools - Cicle I, in Franca-SP, took part in the research. A questionnaire and an interview were used to collect data. Results showed that school professionals recognize the importance of parents/guardian at school, but they also recognize the difficulty to promote it. The study revealed that Parent and Teacher Associations (PTAs) and School Councils could not be firmed yet as effective auxiliary canals for the Education Institutions. On the contrary, the participants consider these canals as formal, bureaucratic spaces: the first, giving priority to the finance dimension, without any connection with the pedagogic dimension; the latter, it is showed through reports, have little performance in the everyday school life. About both Parent and Teacher Association (PTAs) and School Councils it was detected a lack of clearness on the part of the school professionals as for the aims, rights and owes that these canals point, discrediting, thus, the power of decision and participation on them, in the sight of improving education. On the other hand, it was observed a change, at least in the discourse, going towards the recognition that the school is not self-sufficient to take decisions and it needs the parents/guardian to achieve the goal of a school with better quality